Sharing Natural Resource Revenues with Affected Communities : Policy Options for Mozambique - Nombora, Dionisio (World Bank, Washington, DC, 2014)
This note analyzes the institutional and policy context in which Mozambique allocates and manages resource revenues at the subnational level. Its objectives are: (i) to better understand the extent to which the current revenue-sharing system advances the countries stated development goals, (ii) to identify any significant weaknesses or constraints in the current system, and (iii) to provide recommendations for strengthening the policy framework and institutional mechanisms for sharing resource revenues. This analysis is informed by the international experience with allocating and managing resource revenues at the subnational level, and it applies a number of important lessons learned. The policy note is divided into five sections. Section one presents projections for future resource revenue transfers to subnational governments, both in absolute terms and as a share of each district s total budget. Section two reviews the international experience with resource sharing and identifies key lessons to inform successful policies. Section three presents a broader look at fiscal decentralization in Mozambique. Section four discusses the main findings of the analysis and situates them in the context of Mozambique s current revenue-sharing policies. Section five concludes the note by laying out recommendations to improve Mozambique s institutional and policy framework for allocating resource revenues at the subnational level. This policy note is based on a survey of the international literature on fiscal decentralization in general and resource revenue sharing in particular.